Pengaruh Stres Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Renobsindo Jayaraya Mandiri Banjarbaru - Situmorang, Marianti; Karsudjono, Anthonius Junianto (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2023)
This study aims to determine and analyze the effect of work stress and the work environment on the performance of employees of PT Renobsindo Jayaraya Mandiri Banjarbaru both simultaneously, partially and together. The population and sample in this study are all employees, totaling 32 people. The type of research conducted was correlational which emphasized the statistical tests of multiple linear regression analysis, instruments, Likert scale obtained from direct interviews and from questionnaires distributed to all employees of PT Renobsindo Jayaraya Mandiri Banjarbaru. The results of this study indicate that there is a percentage level of 75.7% stating that work stress and the work environment can affect employee performance. The variables that can influence outside the variables in this study are the remaining 24.5%.